دراسة تشريحية مرضية وسريرية لعينات غدّة الموثة في مشفى الأسد الجامعي - أحمد, عيسى يوسف (Latakia University Journal -Medical Sciences Series, 2019)
تعطي ضخامات الموثة السليمة و الخبيثة أعراضاً بولية تؤدي إلى تخريب حياة الإنسان الطبيعية أو تنهي حياة المريض، ولأن الموتى الذين لديهم سرطانة موثة غير مشخصة أكثر من الرجال المشخص لديهم سرطانة أثناء الحياة ، فإنه من الواجب دوماً محاولة البحث عن الأمراض الخطيرة بكل الوسائل السريرية والتشريحية المرضية وذلك عن طريق تكرار أخذ الخزع من الموثة بهدف الكشف المبكر عن السرطانات الكامنة أو الخفية أو السرطانات المتظاهرة سريرياً، ذلك كله بغية العلاج المبكر للأمراض و تحسين إنذارها. تبين الدراسة الإحصائية و التشريحية المرضية لعينات الموثة أن -بغض النظر عن عمر المريض وحجم ووزن الغدة المستأصلة- احتمال وجود أورام خبيثة يبقى وارداً, ويجب البحث في خزعات الموثة عن عوامل الخطر أو التغيرات الشكليائية المؤهبة لنشوء وتطور الخبث الموثي، مثل الالتهاب المزمن والأورام الموضعة ضمن الظهارة وفرط تنسج الخلايا القاعدية أو فرط تنسج الموثة السليم. Benign and malignant prostatic enlargements give urinary symptoms, which lead to the destruction of patient's life or terminating it, and because of the dead who have undiagnosed prostatic carcinoma more than men diagnosed with carcinoma during life, it should always try to search for serious diseases by all available clinical and histopathological methods, such as repeated biopsies of prostate in order to early detect latent or occult cancers and clinically demonstrator cancers, each with a view to treatment of diseases and improve the prognosis. The statistical and histopathologic studies of samples show that regardless of the patient's age and size and weight of the removed gland, the likelihood of the presence of malignant tumors remains an option and must be sought in biopsy prostate risk factors or morphologic changes predisposing to the emergence and development of prostatic malignancy, such as chronic inflammation, intraepithelial neoplasia, basal cell and benign hyperplasia.